2021
DOI: 10.1088/1755-1315/719/3/032023
|View full text |Cite
|
Sign up to set email alerts
|

On the Characteristics of Cold Spray Technology and Its Application in Aerospace Industries

Abstract: Cold spraying technology is an advanced spraying technology developed based on the principles of aerodynamics. It is mainly used to deposit and repair the surface of metal alloy parts to ensure that the parts have better mechanical properties and service life. Compared with traditional thermal spraying technology, cold spraying technology has many advantages, such as low spraying temperature, low oxygen content and low porosity, and it is not easy to cause oxidation, burning, phase change and other phenomena d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…The temperature is also an essential factor affecting deposition efficiency. The influence of gas temperature on critical velocity was shown in [20]. Also, spraying Al particles with a distance of 30 mm and Cu particles with a distance of 15 mm were shown in [1,21].…”
Section: Laval Nozzle's Parameter Designmentioning
confidence: 98%
“…The temperature is also an essential factor affecting deposition efficiency. The influence of gas temperature on critical velocity was shown in [20]. Also, spraying Al particles with a distance of 30 mm and Cu particles with a distance of 15 mm were shown in [1,21].…”
Section: Laval Nozzle's Parameter Designmentioning
confidence: 98%
“…Prior studies [23][24][25][26][27][28][29][30][31][32][33][34] have shown that the level of R t is determined by the coating properties. The R t value increases due to the massive enhancement in the coated region after FSP.…”
Section: Electrochemical Impedance Spectroscopy (Eis)mentioning
confidence: 99%